Wawasan Agama Dan Sosial-Budaya Masyarakat Dalam Penyuluhan Agama - I Gusti Agung Dharmawan; Agung Adi (Widya Sandhi, 2026)
The article aims to explain the relationship between Hindu religious insights and the diversity of socio-cultural backgrounds that must be understood in the context of Hindu religious counseling in society. This is closely related to the ability of Hindu religious counselors to deal with socio-cultural dynamics that also have an impact on the effectiveness of religious counseling. This study uses several literatures that provide an explanation of the importance of understanding the relationship between religion and socio-cultural society. The results of the study revealed that a deeper understanding of religion for a counselor positively correlates with the level of community understanding of religious values, while socio-cultural factors, including local traditions and social norms, play a key role in the process of religious counseling. A deep understanding of local culture allows religious counselors to design more contextual and relevant counseling programs for the community.